Current Topics (The Muslim world, 1939)
A Missionary and a Moslem King Palestine: A Rational View The Trans-Iranian Railway A Nudist Colony in Iraq Los Angeles as Pilgrim Center H. G. Wells Offends Moslems The Rector of the Azhar and the Church of the Holy Sepulchre A Governor of Egypt Honora American Schools The Question of the Khilafat The Tomb of Omar Khayyām Edmonton Mosque First in Canada Closed Moslem Emirates in Nigeria Opened by the Lepers With the Red Kaffirs of the Hindu Khoosh Islam in Czechoslovakia